Satellite data reveal differential responses of Swiss forests to unprecedented 2018 drought. (7th March 2022) - Sturm, Joan; Santos, Maria J.; Schmid, Bernhard; Damm, Alexander
Abstract: Extreme events such as the summer drought of 2018 in Central Europe are projected to occur more frequently in the future and may cause major damages including increased tree mortality and negative impacts on forest ecosystem services. Here, we quantify the response of >1 million forest pixels of 10 × 10 m across Switzerland to the 2018 drought in terms of resistance, recovery, and resilience. We used the Normalized Difference Water Index (NDWI) derived from Sentinel‐2 satellite data as a proxy for canopy water content and analyzed its relative change. We calculated NDWI change between the 2017 pre‐drought and 2018 drought years (indicating resistance), 2018 and the 2019 post‐drought (indicating recovery), and between 2017–2019 (indicating resilience). Analyzing the data from this large natural experiment, we found that for 4.3% of the Swiss forest the NDWI declined between 2017 and 2018, indicating areas with low resistance of the forest canopy to drought effects. While roughly 50% of this area recovered, in 2.7% of the forested area NDWI continued to decline from 2018 to 2019, suggesting prolonged negative effects or delayed damage. We found differential forest responses to drought associated with site topographic characteristics and forest stand characteristics, and to a lesser extent with climatic conditions and interactions between these drivers. Low drought resistance and high recovery were most prominent at forest edges, but also on south‐facing slopes and lower elevations. Tree functional type was the most important driver of drought resilience, with most of the damage in stands with high conifer abundance. Our results demonstrate the suitability of satellite‐based quantification of drought‐induced forest damage at high spatial resolution across large areas. Such information is important to predict how local site characteristics may impact forest vulnerability to future extreme events and help in the search for appropriate adaptation strategies. Abstract : We use the change of the normalized difference water index (NDWI) to detect which forest areas were damaged by the 2018 drought in Switzerland, and the conditions that lead to these effects. We found strongest linear relations between damaged forest and folded aspect, distance to the forest edge, elevation, and forest type. However, the direction and strength of the relationship varied based on the underlying time frame.